A SEMIOTIC ANALYSIS AT INSTAGRAM FILTER - Ifatun Nisak; muyassaroh (English Language Teaching Journal, 2022)
Semiotics has an expression related to sign as a part of human life. In this study,researcher chose the Ferdinand de Saussure Theory to understand the meaning of the signs.Where, in this study, the researcher examined all the signs that appeared in the Instagram filterstarting from the image, sound-imagery, or acoustic imagery, the objects used as signs in thisInstagram video filter. The main aim of this research is to understand the meaning signsconveyed by the creator in the Instagram filter. This research uses a Qualitative research, Theresearcher analyzed data into 3 stages that are data reduction stage, Interpretation stage, andconclusion stage. The finding shows if the most common or commonly found are signifiers in theconcept section, while in the dimensions section they are semantic and pragmatic. It can be saidthat semiotics can be applied and found in various parts of life show personality in representingtheir emotions and memories. So, it can be conclude if humans use signs in their daily lives toshow what they feel and their emotions towards life, both the social environment and so on. Oneof which is through this Instagram filter.Keywords: semiotics, visual sign, instagram filter.